THE MODERATING EFFECT OF THE AUDIT COMMITTEE ON THE RELATIONSHIP BETWEEN ESG PERFORMANCE, TAX AGGRESSIVENESS, AND EARNINGS PERSISTENCE - Efendi Susana; Sistya Rachmawati (KRISNA: Kumpulan Riset Akuntansi, 2026)
In the modern business landscape, organizations are increasingly expected not only to achieve financial profitability but also to demonstrate responsibility toward environmental and social issues, which are commonly represented through Environmental, Social, and Governance (ESG) performance indicators. Meanwhile, the adoption of aggressive tax strategies can create instability in reported earnings and may generate concerns among stakeholders regarding corporate transparency and ethical conduct. This research investigates how ESG performance and tax aggressiveness influence earnings persistence while also analyzing the moderating function of the audit committee as a component of corporate governance. The study uses data from 97 firms listed on the Indonesia Stock Exchange between 2019 and 2021, resulting in 291 firm-year observations obtained through purposive sampling. Panel data regression analysis was conducted using EViews version 12. The findings reveal that ESG performance does not have a statistically significant relationship with earnings persistence. However, tax aggressiveness, proxied by the Effective Tax Rate (ETR), shows a negative association with earnings persistence. In addition, the presence of the audit committee mitigates the adverse effect of tax aggressiveness on earnings persistence. These findings highlight the importance of corporate governance mechanisms in improving financial reporting quality and maintaining earnings sustainability.